The Correlation between Sensitivity of Medical Ethics and Patient Satisfaction - Hepy Hardiyanti Kusumaningtyas; . Maryani; Bulan Kakanita Hermasari (Fakultas Kedokteran Universitas Sebelas Maret Surakarta, 2017)
Introduction: The World Health Organization (WHO) estimates that one million people worldwide suffer from disabilities and even deaths annually as a result of unsafe healthcare practices. This fact requires improving the quality of health services. The quality of these services can be reflected by patient satisfaction. Patient satisfaction is also supported by a doctor-patient relationship and it is the foundation of the medical practice and medical ethics. This study aimed to determine the association between sensitivity of medical ethics and patient's satisfaction. Methods: This research was an observational analytical method with cross sectional approach. Subjects in this study were inpatients and postgraduate medical students at Dr. Moewardi Hospital. The samples of research were taken using the simple random sampling and convenience sampling technique. The data of research were analyzed using Pearsons correlation test. Results: From the results of data analysis, correlation between sensitivity of medical ethics and patient's satisfaction with p = 0.078, which means not statistically significant, but with the moderate correlation power and direction of the correlation was a positive correlation (r = 0.469). Conclusion: There is positive correlation between ethics physicians with patient satisfaction Keyword: Medical Ethics, Patients Satisfaction, Doctor-Patient Relationship